Analysis of the impacts of entrepreneurship training on growth performance of firms: Quasi-experimental evidence from Nigeria. Issue 3 (3rd September 2018) - Efobi, Uchenna; Orkoh, Emmanuel
Abstract : Purpose: Using quasi-experimental designs, the purpose of this paper is to study the effects of training entrepreneurs and such entrepreneurs going ahead to retrain its workers on the business high-growth performance. Design/methodology/approach: This paper used a unique evaluation data from the National Business Plan Competition in Nigeria, organized by the Nigerian government in collaboration with the World Bank. The data was analyzed using the Propensity Score Matching technique and complemented with the Difference-in-Difference estimates. Findings: The authors find from the estimation of this paper that those entrepreneurs who received standard evaluation training and goes ahead to retrain its workers experienced an expansion in the number of employees by two persons, an increase in innovation index by about 3 units. An increase in revenue is also observed, but this increase was not significant at the 1, 5 or 10 per cent levels. Originality/value: This paper presents an interesting view point on how training within an entrepreneurial venture should be viewed as a 'two sided coin'. This is such that training the entrepreneur is one side of the story, and the entrepreneur retraining its workers is another important side of the story.